Introduction to physical education. exercise science, and sport - Lumpkin, Angela B.S.E., M.A., M.B.A., Ph.D (McGraw Hill, 2021)
The eleventh edition provides the latest information about physical education, the exercise science, and sport as professional career options. Each chapter has been updated and includes some of the latest research to stimulate students' critical thinking and continued study. Review questions, boxed material, student activities, key points, and web connections have been revised and updated